'Important Trifles': Jane Austen, the fashion magazine, and inter-textual consumer experience. Issue 2 (3rd May 2016) - Taylor, Jane
ABSTRACT: Austen's letters, maligned by E. M. Forster, a self-confessed 'Jane Austenite', as 'catalogues of trivialities which do not come alive', have in many ways brought to life the consumer world of the late eighteenth century. However, we cannot pass over Austen's letters as simple historical records of how and where the author participated in a burgeoning consumer culture. Rather, we must consider them alongside her fiction as literary artefacts actively engaging with the rising fashion system. In her letters and early fiction Austen cultivates a style that is precariously positioned between satire and earnestness in her depiction of consumer experience, celebrating ambivalence and paradox. This article reads Austen's playful linguistic representations of the trifles of fashionable consumption alongside the flourishing market of fashion-related literature, in particular the nascent fashion magazine. In doing so, it reveals the diverse ways in which these magazines, like Austen's letters and fiction, both contested and aggrandised the triviality of fashionable consumption. This article seeks to reassess – indeed recover – fashion magazines of the late-eighteenth century, publications which have been largely overlooked by historians and literary critics, in order to conceptualise the textual experience of fashionable consumption in the period.